Bioassay-Guided Fractionation of the Active Constituent of Juniperus Chinensis - Ismail, Intan Safinar (1997)
Deoxypodophyllotoxin, a lignan, was afforded from the bioassay-guided fractionation of the EtOAc soluble part of the leaves and twigs of Juniperus chinensis. The fractionation was directed by microtitration cytotoxicity assay employing human cervical adenocarcinoma (HeLa) cell line. The activity was visible by fixing and staining the cells and comparing the number of cell reduction by the active agent with the confluent controls. A judicious combination of chromatographic techniques was adopted in purifying the active compound from the crude complex. The structure of the isolated lignan was elucidated using spectroscopic techniques including ultraviolet spectroscopy (UV), infrared spectroscopy (IR), nuclear magnetic, resonance spectroscopy (¹H and ¹³C-NMR), mass spectroscopy (MS), and also by comparison with the literature.The cytotoxic concentration of deoxypodophyllotoxin which caused up to almost 100% reduction of HeLa cells was determined as 0.004 Jlg/ml. Cytotoxic activity of this lignan was further evaluated on different types of specific human organ tumour cell lines: KU8 12F (Chronic mylogeneous leukemia), TK-10 (Renal carcinoma), UACC-62 (Melanoma) as well as CEM-SS (T-cell lymphoblastic leukemia). All of the tumour cell lines studied were found to be susceptible to deoxypodophyllotoxin, nevertheless, the degree of susceptibilities was different between cell lines. Minimum effective concentration (MEC) with almost 1 00% reduction of the cells were observed in HeLa (0.004 µg/ml), TK-10 (0.01 µg/ml), UACC-62 (0.004 µg/ml) and CEM-SS (0.01 µg/ml). Whilst KU8 12F (0.04 µg/ml) inhibited only 50% the cell growth (ECso). Thus, the most sensitive cell l ines towards the treatment of the lignan were HeLa and UACC-62. Antimicrobial disc diffusion assay (Bauer et al., 1966) on deoxypodophyllotoxin was carried out employing gram positive bacteria (Bacillus megaterium, Bacillus cereus, Bacillus subtilis, Flavobacterium meningosepticum, Slaphylloccus aureus, Micrococcus luleus, Chrysomollas leuteola and Aeromonas salmonella), and gram negative bacteria (Pseudomonas aeruginosa, Pseudomonas paucinobilis, Pseudomonas capacia and Escherichia coli), and on yeast (Torulopsis glabrata, Crytococcus neoformans, Saccharomyces lipolytica, Candida albicans, Candida lipolytica and Candida inlermedia), and also a fungi (Aspergillus ochraceous). The growth of most of the organisms were inhibited by deoxypodophyllotoxin at the concentration of 10 mg/ml by producing a clearing zone with diameter ranging between 8 to 12 mm with the exception of Pseudomonas aeruginosa, P. paucinobilis, Aeromonas salmonella and Candida intermedia.